The contribution of information management to administrative decision making in Kinondoni Municipal Council - Hitler, Sanchawa D (Mzumbe University, 2024)
Thesis submitted to the School of Public Administration and Management in partial fulfillment of the requirements for the Award of the Degree of Master of Public Administration (MPA) of Mzumbe University